Molecular Radiation Biology - Reindl, Judith; Abrantes, Ana Margarida; Ahire, Vidhula; Azimzadeh, Omid; Baatout, Sarah; Baeyens, Ans; Baselet, Bjorn; Chauhan, Vinita; Da Pieve, Fabiana; Delbart, Wendy; Dobney, Caitlin Pria; Edin, Nina Frederike Jeppesen; et al. (Springer International Publishing, 2023)
Various exogeneous and endogenous factors constantly cause damages in the biomolecules within a cell. For example, per day, 10,000-100,000 molecular lesions occur in DNA per cell. The molecule modifications that are formed disturb the structure and function of the affected molecules. The purpose of this chapter is to introduce the damages to biomolecules caused by radiation, the associated repair pathways, and the effect on the cellular function. Special interest lies on the damages induced to DNA, the carrier of the human genome, and the consequence to genomic integrity, cell death, and cell survival. Additionally, related effects regarding inflammation and immunity, epigenetic factors, and omics are discussed. The chapter concludes with an explanation of the molecular factors of cellular hyper-radiosensitivity and induced radiation resistance.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Apoptosis; Autophagy; Epigenetic modifications; Extracellular vesicles; Necrosis; Noncoding RNAs; Radiation response biomarkers